Prevalence of induced abortions and contraceptive use among married women in an urban slum of Delhi, India. Issue 1 (3rd November 2016) - Bhilwar, Meenakshi; Lal, Panna; Sharma, Nandini; Bhalla, Preena; Kumar, Ashok
Abstract: Objective: To document abortion practices and contraceptive use among women of reproductive age in an urban slum of Delhi. Methods: Data were collected as part of a cross‐sectional study conducted in an urban resettlement colony in the North East District of Delhi between November 2010 and December 2011. Systematic random sampling was used to enroll 200 married women aged 15–49 years from each of the four blocks of the colony. Participants were interviewed and data were entered into a pretested semi‐structured questionnaire. Results: Among 802 participants, 284 (35.4%) reported at least one spontaneous or induced abortion, and 196 (24.4%) reported induced abortions. Unsupervised medical termination was reported by 78 (27.5%) of the 284 women. Overall, only 207 (25.8%) women practiced any type of contraception. The predominant decision maker regarding contraception was the husband for 95 (45.9%) women and the mother‐in‐law for 78 (37.7%). Conclusion: There is a need for focused community‐based education to address specific issues, particularly regarding the dangers of unsafe abortion and choosing a method of contraception in consultation with a healthcare practitioner. Abstract : Frequency of induced abortion is fairly high among married women in an Indian urban slum. By contrast, autonomy in terms of contraceptive choices is low.